A alta capacidade pela perspectiva das mulheres: estudos de caso do Brasil e da Espanha - Massuda, Mayra Berto (Universidade Federal de São Carlos, 2019)
The finding that national and international studies on women's giftedness are still incipient in light of the universe of research already conducted on human intelligence highlights the inequality in the identification and development of gifted girls and women, as well as internal and external barriers faced by them. From this, the main objective of this study was to identify and analyze the barriers that hinder the identification and development of gifted girls in two different educational contexts, in Brazil and in Spain, and to propose actions to overcome these barriers within the context of conceptualization, identification and educational service of each country. The secondary objectives were: a) contextualize the concepts, strategies of identification and educational assistance to gifted students through case studies of a local program in Brazil and another in Spain; b) identify and analyze the barriers that hinder the diagnosis and development of the potential of girls with giftedness in procedures, mediations and personal experiences; c) reveal how these barriers are addressed by their service management, families and professionals involved. Thus, we conducted a qualitative research with a feminist critical perspective with the Collective Subject Discourse method. We used documentary research and problem-centered interviews as techniques to collect data, considering that the documentary research was based on legal documents that allowed contextualizing the processes of identification and attendance to the gifted students of each investigated locality, besides the statistical data regarding the enrollment of male and female students with iftedness. The interviews were analyzed following the methodological proposal of the Collective Subject Discourse and the results of the analyzes were organized in two Case Studies: one related to the study conducted in a city of the autonomous community of Andalusia, Spain; and one related to a study conducted in a city in the state of Minas Gerais, Brazil. Thus, 7 female students (8 to 16 years) from Spain and 7 female students (11 to 18 years) from Brazil were the main participants in the study. The results showed that in both Brazil and Spain, the national average of formally identified girls with giftedness is lower than the number of boys, and in the Spanish city, the proportion of girls is higher than the national average, but even lower that the average of boys; and in the Brazilian city, the proportion of girls is higher than the proportion of boys. The analysis of interviews with girls with giftedness in Brazil and Spain, pointed to the existence of the following gender bias as the main barriers to the identification and development of their potential: the need to be or look perfect, the impostor syndrome, the willingness to help or care, and the complacent leadership model. In this sense, access to specific care programs for the development of giftedness, motivation in the educational and family environment, the existence of mentors and women who are models of potential realization, are fundamental factors for the confrontation of gender bias.

El hecho de que los estudios nacionales e internacionales sobre la alta capacidad femenina siguen siendo escasos en el universo de la investigación científica ya realizada acerca de la inteligencia humana, pone de relieve la desigualdad en la identificación y desarrollo de las niñas y mujeres con alta capacidad, así como las barreras internas y externas que ellas enfrentan. A partir de eso, el objetivo general de esta investigación fue indentificar y analizar las barreras que dificultan la identificación y el desarrollo de niñas con alta capacidad en dos contextos de atención educativa diversos como son los de Brasil y España y proponer acciones para la superación de esas barreras en el contexto de conceptualización, identificación y atención educativa de cada país. Los objetivos secundarios son: a) contextualizar los conceptos, las estrategias de identificación y atención educativa a alumnos y alumnas con alta capacidad a través de los estudios de caso de un programa local de Brasil y en otro de España; b) identificar y analizar las barreras que dificultan el diagnóstico y el desarrollo de las potencialidades de las niñas con alta capacidad en los procedimientos, mediaciones y experiencias personales; c) desvelar cómo se afrontan las barreras desde la gestión de los programas, las familias y las propias implicadas. Así, se aplicó una investigación cualitativa con una perspectiva crítica feminista con el método del Discurso del Sujeto Colectivo. Las técnicas de recogida de datos fueron la investigación documental y entrevistas centradas en el problema siendo que la investigación documental se basó en los documentos legales que permitieran contextualizar los procesos de identificación y atención a la alta capacidad de cada localidad investigada, y en los datos estadísticos referentes a las matrículas de alumnos y alumnas con alta capacidad. Las entrevistas fueron analizadas siguiendo la propuesta metodológica del Discurso del Sujeto Colectivo y los resultados de los análisis fueron organizados en dos Estudios de Caso: uno relativo al estudio realizado en una ciudad de la comunidad autónoma de Andalucía, España; y otro relativo al estudio realizado en una ciudad del estado de Minas Gerais, Brasil. De esta forma, fueron las participantes principales de la investigación 7 alumnas (8 a 16 años) de España y 7 alumnas (11 a 18 años) de Brasil. Los resultados señalan que, tanto en Brasil como en España, el promedio nacional de niñas formalmente identificadas con alta capacidad, es inferior al número de niños, siendo que, en la ciudad española, la proporción de niñas es mayor que el promedio nacional, pero aún menor que el promedio de niños; y en la ciudad brasileña, la proporción de niñas es mayor que la proporción de niños. El análisis de las entrevistas con las niñas con alta capacidad en Brasil y España, señalan la existencia de los siguientes códigos de género como las principales barreras para la identificación y desarrollo de su potencial: la necesidad de ser o parecer perfecta, el síndrome de la impostora, la disposición en ayudar o cuidar y el modelo de liderazgo complaciente. En este sentido, el acceso a programas de atención específica para el desarrollo de la alta capacidad, la motivación en el ambiente educativo y familiar, la existencia de mentoras y mujeres que son modelo de realización del potencial, son factores fundamentales para el enfrentamiento de los códigos de género.
Giftedness from the perspective of women: case studies from Brazil and Spain
Altas capacidades desde la perspectiva de las mujeres: estudios de caso de Brasil y España
Keywords: Educação especial; Alta capacidade; Gênero; Special education; Giftedness; Gender; Women education; Educación especial; Alta capacidad; Género; Educación de la mujer; Educação da mulher; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO